An evaluation of relugolix/estradiol/norethindrone acetate for the treatment of heavy menstrual bleeding associated with uterine fibroids in premenopausal women. (4th March 2022) - Ali, Mohamed; Chen, Hsin-Yuan; Chiang, Yi-Fen; Badary, Osama A; Hsia, Shih-Min; Al-Hendy, Ayman
ABSTRACT: Introduction: Uterine Fibroids (UFs) are the most predominant benign tumor in women who are coming of reproductive age, and causes intense economic load priced in billions of US dollars. Historically, surgery has been the main definitive treatment, albeit less attractive nowadays, especially for women with future fertility plans. Therefore, studies to explore the pharmacological treatment options are increasing especially as those that are currently available are limited for short-term use only. Areas covered: This drug evaluation features the clinical results from previous and ongoing studies of relugolix, in combination with the add back therapy of estradiol (E2) and norethindrone acetate (NETA), as a novel, orally administered, nonpeptide antagonist of gonadotropin-releasing hormone (GnRH) for the management of heavy menstrual bleeding (HMB) in premenopausal women with UFs. Expert opinion: The combination of relugolix/E2/NETA is an encouraging, well-tolerated and noninvasive pharmacological option for UFs patients. Relugolix induced a concentration-dependent decrease in HMB. However, it should be used with hormonal add-back therapy (E2+ NETA) to avoid induced hypoestrogenic side effects, importantly bone mineral density loss. Moreover, symptoms will likely resume shortly after the termination of the relugolix combination administration.